Role of physical activity on mental health and academic performance among medical students: a cross-sectional study - Jose, Joseph; M. V., Sruthi (International Journal Of Community Medicine And Public Health, 2019)
Background: World Health Organization (WHO) defines physical activity as “any bodily movement produced by skeletal muscles that requires energy expenditure. Since medical education is considered stressful due to voluminous academics, it leaves little time for the students to relax and recreate. Hence the present study had been undertaken with an aim to study various trends of physical activity, health status and academic performance among medical students and to find out any association between physical activity and health status, academic performance of medical students. Methods: A cross-sectional study had been undertaken among 2nd and 3rd year MBBS students of our medical college. Physical activity was assessed using GPAQ version 2 questionnaire and mental status of students was measured using hospital anxiety and depression scale. Height, weight, and BMI, of each student along with demographic details were collected. The total percentage of any one of the internal marks of each student was taken for assessing the academic performance. Results: Out of total 150 medical students it was found that 44% of medical students were physically inactive and 40.7% of them were highly active. Majority of female students 70.3% were physically inactive and overweight and obesity were higher among them when compared with male students. But anxiety and depressive symptoms were higher among male students. There was statistically significant difference in association between level of physical activity and mental health. The academic performance also increased with increase in physical activity. Conclusions: Physical activity and mental health are related proportionally and it bears a positive influence on the education of the youth. The regular physical activity improves the mental status and academic performance among students.